Psycho-Educational Assessments: Theory and Practice (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Psycho-educational assessments, such as intelligence tests, cognitive test batteries and behavioral measures, serve as invaluable tools for school psychologists and educators. They provide profound insights into children's learning and behavioral profiles, enhancing our understanding of their academic and cognitive capacities. This reprint of the Special Issue titled "Psycho-Educational Assessments: Theory and Practice" includes a collection of sixteen articles that delve into the different facets of psycho-educational assessments. Each article serves as a testament to our remarkable journey in understanding and enhancing the psycho-educational assessment landscape, from exploring the efficacy of psycho-educational assessments in diagnosing a range of learning difficulties to different statistical techniques for analyzing psycho-educational constructs, such as local structural equation models and multidimensional scaling. As the editor of this Special Issue, I anticipate that the articles showcased herein will serve as catalysts for meaningful discourse, igniting innovative ideas and enriching the ongoing evolution of psycho-educational assessment.